TRUST IN PURCHASING DECISIONS AT PT CAHAYA SATU JANUARI KARIMUN GAS STATIONS - Roja Mazalifah; Wasiman Wasiman (SEAN Institute, 2023)
Fuel is a community need, with various types of fuel available, each community consumes fuel according to their respective abilities, some see it from a price perspective and some look at it from the quality side offered. People's purchasing decisions are influenced by work, income, product quality, trust and several other factors. Various types of fuel are offered with different quality and prices. Community consumption of fuel, especially in Karimun Regency, is still dominated by pertalite because people see it from a price perspective, where the price is pertalite is cheaper compared to other types of fuel. The purchasing power of this community is of course influenced by the work and income earned and several other supporting factors. The population used in this research was 150 with an error rate of 5% so that a total of 123 samples were obtained. The results of this study indicate that there is a significant influence between product quality, consumer behavior and trust in purchasing decisions at the Cahaya Satu January Karimun gas station. Based on the analysis of the f test, it can be seen from the significant value (0.000 <0.05) and the Fcount value of 127.420 > Ftable 3.06. This means that product quality variables (X1), consumer behavior (X2) and trust (X3) have a significant effect on purchasing decision variables